You're Doing It Wrong. - KAMP, POUL-HENNING (Communications of the ACM, 2010)
The article presents a method for improving the performance of a computer algorithm for HTTP web servers. It makes use of virtual memory to cache objects which would otherwise slow down the system. The concepts involved are explained in terms of the binary heap runtime speed, and it is noted that improvements in server speed of up to an order of magnitude can be obtained under normal conditions. Open source software for implementing these ideas is described, which has been used by websites such as Facebook and Slashdot.